2014
DOI: 10.1016/j.tibs.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Marching to the beat of the ring: polypeptide translocation by AAA+ proteases

Abstract: ATP-dependent proteases exist in all cells and are crucial regulators of the proteome. These machines consist of a hexameric, ring-shaped motor responsible for engaging, unfolding, and translocating protein substrates into an associated peptidase for degradation. Here, we discuss recent work that has established how the six motor subunits coordinate their ATP-hydrolysis and translocation activities. The closed topology of the ring and the rigidity of subunit/subunit interfaces cause conformational changes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 59 publications
1
43
0
1
Order By: Relevance
“…A consequence of this organization is that the aromatic hydrophobic (Ar-Φ) "pore loops," which project into the central pore of the heterohexamer, arrange in a spiral staircase. These pore loops are thought to pull the substrate into the CP (32). Although in previous intermediate-resolution studies of the yeast 26S proteasome the precise position of the Ar-Φ pore loops has been inferred from the fitted structures of Rpt homologs, the highresolution map of the human 26S proteasome now reveals the proteasomal Ar-Φ pore loops directly (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…A consequence of this organization is that the aromatic hydrophobic (Ar-Φ) "pore loops," which project into the central pore of the heterohexamer, arrange in a spiral staircase. These pore loops are thought to pull the substrate into the CP (32). Although in previous intermediate-resolution studies of the yeast 26S proteasome the precise position of the Ar-Φ pore loops has been inferred from the fitted structures of Rpt homologs, the highresolution map of the human 26S proteasome now reveals the proteasomal Ar-Φ pore loops directly (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The AAA + ATPase is lined by aromatic-hydrophobic loops (pore-1 loops), which grab and pull polypeptides. Driven by ATP binding and hydrolysis, the pore-1 loops undergo conformational changes threading the polypeptide through the central channel, similar to the mechanism postulated for the bacterial ATP-dependent caseinolytic protease X (ClpX) (19,20). Our previous study revealed the existence of three distinct conformational states (21).…”
mentioning
confidence: 74%
“…Like other AAA + ATPase family members, the nucleotide-binding pocket is formed by five conserved motifs: Walker A, Walker B, sensor I, sensor II, and Arg-finger. The nucleotide is located at the "interface module," defined by a small domain of one Rpt subunit and the large domain of its clockwise adjacent Rpt subunit (20,33). In the s1 state, the interface module units are closely connected to each other, except at the split site between Rpt6 and Rpt3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The state s3 is only populated in the presence of the slowly hydrolysable ATP analog ATP-γS, suggesting that this is a high-energy prehydrolysis state with a maximum number of nucleotides bound. Like other AAA-ATPases (34,35) the 26S proteasome appears to bind a maximum of four nucleotides (15). In the bacterial RP homolog ClpX the two unoccupied ATP-binding sites are suggested to be in opposite positions of the hexameric ring with one site being in an unloadable conformation and the other site is in a loadable state (36).…”
Section: Discussionmentioning
confidence: 99%